OPTIMIZATION OF EXTRUSION COOKING PROCESS FOR CHICKPEA (CICER-ARIETINUM, L) DEFATTED FLOUR BY RESPONSE-SURFACE METHODOLOGY - Batistuti, J. P.; Barros, RMC; Areas, JAG (Inst Food Technologists, 1991)
Response surface methodology was employed to optimize the production of a snack food from chickpea. The independent variables, process temperature (123-137-degrees-C) and feed moisture (13-27% d.s.b.) were selected at five levels (rotatable five level composite design: - square-root 2, -1, 0, 1, + square-root 2) in the extrusion of defatted chickpea flour. Response variables were expansion ratio, shear strength of the extrudate and sensory preference assessed by an untrained panel. Expansion ratio increased steadily with decrease in feed moisture similar to cereal extrusion. Regions of maxima were observed for sensory preference and shear strength, and these two product attributes were linearly related. The most acceptable chickpea snack was rated higher than a commercial corn snack.